2022
DOI: 10.1016/j.isci.2021.103688
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular mechanisms underlying vocal behavior in freely moving macaque monkeys

Abstract: Summary Communication is a keystone of animal behavior. However, the physiological states underlying natural vocal signaling are still largely unknown. In this study, we investigated the correlation of affective vocal utterances with concomitant cardiorespiratory mechanisms. We telemetrically recorded electrocardiography, blood pressure, and physical activity in six freely moving and interacting cynomolgus monkeys ( Macaca fascicularis ). Our results demonstrate that vocal ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Furthermore, they have been shown to be capable of adaptively modifying distinct call features, such as call frequency, amplitude and duration, in response to external acoustical stimuli [23][24][25]. Recently, it has been revealed that marmosets exhibit synchronized and phase-locked phono-articulatory movements suggesting that such speech-like bi-motor oscillations, which are crucial for speech production, evolved early in the primate lineage [26]. While we cannot go back in time to observe evolution, we can recreate scenarios with selective pressures to find out how vocal systems adapt [1].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they have been shown to be capable of adaptively modifying distinct call features, such as call frequency, amplitude and duration, in response to external acoustical stimuli [23][24][25]. Recently, it has been revealed that marmosets exhibit synchronized and phase-locked phono-articulatory movements suggesting that such speech-like bi-motor oscillations, which are crucial for speech production, evolved early in the primate lineage [26]. While we cannot go back in time to observe evolution, we can recreate scenarios with selective pressures to find out how vocal systems adapt [1].…”
Section: Introductionmentioning
confidence: 99%